Adipocyte DIO2 Expression Increases in Human Obesity but Is Not Related to Systemic Insulin Sensitivity. (15th July 2018) - Bradley, David; Liu, Joey; Blaszczak, Alecia; Wright, Valerie; Jalilvand, Anahita; Needleman, Bradley; Noria, Sabrena; Renton, David; Hsueh, Willa
Abstract : Deiodinase type II (D2), encoded by DIO2, catalyzes the conversion of T4 to bioactive T3. T3 not only stimulates adaptive thermogenesis but also affects adipose tissue (AT) lipid accumulation, mitochondrial function, inflammation, and potentially systemic metabolism. Although better defined in brown AT, the precise role of DIO2 expression in white AT remains largely unknown, with data derived only from whole fat. Therefore, the purpose of this study was to determine whether subcutaneous (SAT) and visceral (VAT) adipocyte-specific gene expression of DIO2 differs between obese and lean patients and whether these differences relate to alterations in mitochondrial function, fatty acid flux, inflammatory cytokines/adipokines, and ultimately insulin sensitivity. Accordingly, adipocytes of 73 obese and 21 lean subjects were isolated and subjected to gene expression analyses. Our results demonstrate that obese compared to lean human individuals have increased adipocyte-specific DIO2 expression in both SAT and VAT. Although higher DIO2 was strongly related to reduced fatty acid synthesis/oxidation and mitochondrial function, we found no relationship to proinflammatory cytokines or insulin resistance and no difference based on diabetic status. Our results suggest that adipocyte-derived DIO2 may play a role in weight maintenance but is likely not a major contributor to obesity-related insulin resistance.